2020
DOI: 10.1038/s41598-020-76180-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a cryptic parasitoid species reveals its suitability as a biological control agent

Abstract: Uncertainty about the taxonomic status and the specificity of a species commonly prevent its consideration as a candidate for biological control of pest organisms. Here we use a combination of molecular analysis and crossing experiments to gather evidence that the parasitoid wasp Ganaspis brasiliensis, a candidate for biological control of the invasive spotted wing drosophila Drosophila suzukii, is a complex of at least two cryptic species. Complementary experiments demonstrate that individuals from one geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
(87 reference statements)
1
20
0
Order By: Relevance
“…In contrast, the two figitids had narrower physiological host ranges, especially the more host-specific populations of G. brasiliensis (G1 and G3) (Daane et al 2016;Giorgini et al 2019;Girod et al 2018b;Matsuura et al 2018;Nomano et al 2017;Seehausen et al 2021). Moreover, host phylogeny strongly influenced the success rate of parasitism in both figitids.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, the two figitids had narrower physiological host ranges, especially the more host-specific populations of G. brasiliensis (G1 and G3) (Daane et al 2016;Giorgini et al 2019;Girod et al 2018b;Matsuura et al 2018;Nomano et al 2017;Seehausen et al 2021). Moreover, host phylogeny strongly influenced the success rate of parasitism in both figitids.…”
Section: Discussionmentioning
confidence: 95%
“…Other researchers reported that G1 populations collected from D. suzukii-infested cherries in Japan specialize on D. suzukii (Girod et al 2018b;Matsuura et al 2018;Nomano et al 2017). Seehausen et al (2021) suggest G1 and G3 are, in fact, cryptic species that can be differentiated by acid-soluble insect protein spectra, some host-searching behaviors, and incompatible crossing.…”
Section: Host Speciesmentioning
confidence: 99%
“…Biological control is a promising route to reduce D. suzukii infestation using natural enemies and insect pathogens (Becher et al 2018;Biondi et al 2020;Daane et al 2016;Gabarra et al 2015;Lee et al 2019;Wolf et al 2020). Findings on the specificity of parasitoids with respect to Drosophila host species, different fruit species as well as fruit ripeness give grounds for hope toward the development of biological control (Girod et al 2018;Wolf et al 2020;Biondi et al 2020;Seehausen et al 2020). In our trap captures, nontargeted Coleopterans and Hymenopterans were recorded but not identified.…”
Section: Discussionmentioning
confidence: 95%
“…The possible existence of natural enemies in the area warrants follow-up studies. Generally, D. suzukii is not limited to sites of fruit production but is often found in forests or unmanaged areas which emphasizes the need for area-wide and long-term control strategies exploiting approaches such as biological control or the sterile insect technique (Haye et al 2016;Seehausen et al 2020;Nikolouli et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, were O. labotus to be considered for biological control of an invasive oak-galling wasp, selecting a population to draw from based on a concept of O. labotus prior to this paper would likely result in failure (1/N; where N is the number of new OTUs), whereas we now know that host ranges are narrow and careful selection from appropriate sources would be important. Several prominent examples demonstrate the importance of this idea to parasitoids of insect agricultural pests (e.g., Heraty et al 2007, Forbes et al 2009, Hood et al 2015, Paterson et al 2016, Seehausen et al 2020 From a basic science standpoint, clarifying the putative axes along which lineages specialize, as well as which components play crucial roles in species diversification will improve our ability to study how parasites evolve. Many studies have used host range data to ask synthetic questions about the relationship between host specialization and diversification (Winkler and Mitter 2008, Armbruster and Muchhala 2009, Novotny et al 2012, Ebel et al 2015, Forbes et al 2017.…”
Section: Hidden Specialists -Why It Mattersmentioning
confidence: 99%